2007
DOI: 10.1096/fj.07-8598com
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of xeroderma pigmentosum group A (XPA) in progeria arising from defective maturation of prelamin A

Abstract: Cellular accumulation of DNA damage has been widely implicated in cellular senescence, aging, and premature aging. In Hutchinson-Gilford progeria syndrome (HGPS) and restrictive dermopathy (RD), premature aging is linked to accumulation of DNA double-strand breaks (DSBs) which results in genome instability. However, how DSBs accumulate in cells despite the presence of intact DNA repair proteins remains unknown. Here we report that the recruitment of DSB repair factors Rad50 and Rad51 to the DSB sites, as marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 46 publications
4
129
0
Order By: Relevance
“…Because the function of DNA repair proteins and chromatinremodeling enzymes is dependent on their proper positioning on the nuclear matrix (32), we hypothesize that the extra 18 amino acids at the carboxyl terminus of unprocessed prelamin A severely reduces the binding of Mof on the nuclear matrix and disrupts its histone acetylation functions. Intriguingly, apart from Mof, progerin expression has been shown to contribute to the mislocalization of ATR, SKIP, and XPA and to the degradation of NURD chromatin-remodeling complex subunits (16,29,(33)(34)(35). The critical question that arises from these reports is why unprocessed lamin A expression elicits such pleiotropic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Because the function of DNA repair proteins and chromatinremodeling enzymes is dependent on their proper positioning on the nuclear matrix (32), we hypothesize that the extra 18 amino acids at the carboxyl terminus of unprocessed prelamin A severely reduces the binding of Mof on the nuclear matrix and disrupts its histone acetylation functions. Intriguingly, apart from Mof, progerin expression has been shown to contribute to the mislocalization of ATR, SKIP, and XPA and to the degradation of NURD chromatin-remodeling complex subunits (16,29,(33)(34)(35). The critical question that arises from these reports is why unprocessed lamin A expression elicits such pleiotropic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the Xeroderma Pigmentosum group A (XPA) protein, an unique nucleotide excision repair protein, localizes to or near DSBs in HGPS and RD cells. 33 The mislocalization of XPA to the DSBs sites inhibits their repair, thus suggesting a role of XPA in the genome instability observed in progeria disorders arising from genetic defects in the prelamin A maturation. 33 Alternatively, the persistence of unresolved repair foci might reflect the presence of stalled replication complexes at sites of DNA damage, either caused by defects in the repair machinery or by aberrant progression due to the altered lamin network.…”
Section: Discussionmentioning
confidence: 99%
“…33 The mislocalization of XPA to the DSBs sites inhibits their repair, thus suggesting a role of XPA in the genome instability observed in progeria disorders arising from genetic defects in the prelamin A maturation. 33 Alternatively, the persistence of unresolved repair foci might reflect the presence of stalled replication complexes at sites of DNA damage, either caused by defects in the repair machinery or by aberrant progression due to the altered lamin network. 27 The response to DNA damage involves the activation of complex checkpoint signalling pathways that delay the cell cycle progression and permit the repair of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of progerin and farnesylated prelamin A has been correlated with defective DNA repair mechanisms and genomic instability [93][94][95]. Progerin binds to DNA-dependent protein kinase catalytic subunit, which functions in genomic stability [96].…”
Section: Pathophysiology and Potential Treatmentsmentioning
confidence: 99%